2015
DOI: 10.5897/ajbr2015.0846
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, fractionation and assessment of antioxidant activities of active components of Aframomum sceptrum seeds

Abstract: A simple procedure of extraction, fractionation and assessment of organoleptic and antioxidant properties of Aframomum sceptrum seeds was carried out, and the results were compared with a currently used synthetic antioxidant, butylated hydroxy toluene (BHT). Extraction was carried out using Soxhlet extractor and fractionation of the ethanolic extract was accomplished using vacuum liquid chromatography (VLC). Various fractions of the ethanolic extract were obtained but similar fractions were pooled together to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fresh leaves of P. biglobosa were collected from a farm in Mkpor, Nsukka LGA of Enugu State, Nigeria and authenticated by John Nwachukwu, a taxonomist at the University of Nigeria, Nsukka and voucher specimen was submitted at the herbarium of Department of Plant Science and Biotechnology (UNH/147). Air-dried and powdered sample was defatted using n-hexane and then extracted by maceration in methanol for 48 h. The filtrate was dried at 40ºC to obtain the crude methanol extract which was fractionated by vacuum-liquid chromatography as described by Nwankwo [13] using silica gel as stationary phase. The solvent fractions were collected and evaporated to dryness and stored at 2-8 o C. Pilot study showed that ethyl acetate fraction (EAFPB) was more active and was then chosen for intervention study.…”
Section: Plant Samplementioning
confidence: 99%
“…Fresh leaves of P. biglobosa were collected from a farm in Mkpor, Nsukka LGA of Enugu State, Nigeria and authenticated by John Nwachukwu, a taxonomist at the University of Nigeria, Nsukka and voucher specimen was submitted at the herbarium of Department of Plant Science and Biotechnology (UNH/147). Air-dried and powdered sample was defatted using n-hexane and then extracted by maceration in methanol for 48 h. The filtrate was dried at 40ºC to obtain the crude methanol extract which was fractionated by vacuum-liquid chromatography as described by Nwankwo [13] using silica gel as stationary phase. The solvent fractions were collected and evaporated to dryness and stored at 2-8 o C. Pilot study showed that ethyl acetate fraction (EAFPB) was more active and was then chosen for intervention study.…”
Section: Plant Samplementioning
confidence: 99%
“…It has been widely researched and reported to be rich in phytochemicals and possess several ethnopharmocological properties; thus, it is reported for its efficacy in the traditional herbal management of malaria [14], wound healing, management of postnatal malignancies after delivery [15] and the treatment of several models of diabetes mellitus [16,17]. The efficacy of A. sceptrum extracts has been explored in the preservation of food products like meat and the oxidative deterioration of palm oil [18,19]. Its efficacy in the prevention of cyanide toxicity in Wistar rats has been reported by Atinaya, D.U et al, [20].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%